DETERMINANTS OF SOYBEAN IMPORT DEPENDENCE IN INDONESIA - Ni Made Sari Ratna Kumala Dewi; Anak Agung Bagus Putu Widanta (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
The phenomenon of soybean import dependence in Indonesia refers to a chronic condition in which the majority of the country’s soybean demand is met through imports due to the highly limited and declining domestic production. Soybeans are a strategic food commodity in Indonesia, particularly as the primary raw material for tofu and tempeh, which are widely consumed by the population. However, the high Import Dependency Ratio (IDR) for soybeans reaching 90.05% in 2021 indicates that Indonesia remains heavily reliant on imported supplies to meet domestic needs. This dependence poses risks to national food security due to global price fluctuations, exchange rate volatility, and potential distribution disruptions. This study aims to analyze the effects of soybean production, soybean consumption, inflation, and the Rupiah-to-USD exchange rate on soybean import dependence in Indonesia. A quantitative approach was employed, using multiple linear regression models with annual time series data from 1989 to 2023. The dependent variable is the Import Dependency Ratio (IDR), while the independent variables consist of soybean production, soybean consumption, inflation, and the U.S. Dollar exchange rate. The results reveal that, partially, soybean consumption and the exchange rate have a positive influence on soybean import dependence, while soybean production and inflation have a negative influence. Simultaneously, all four variables significantly affect the IDR. The findings suggest the need for strategies to boost domestic production and stabilize the exchange rate to reduce soybean import dependence and strengthen national food security.